2017
DOI: 10.1007/s10902-017-9879-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Mood Changes

Abstract: The study explores the influence of individual tendencies toward mood improvement/deterioration and the Big Five personality traits on mood changes. Participants (218 students) completed NEO-FFI and The Mood Regulation Scales. Based on the within-person structure of individual tendencies toward mood improvement/deterioration four mood regulative types were distinguished (increasing, decreasing, hot and cool type). In the experimental stage participants were randomly assigned to one of four group conditions cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Previous studies showed that people with high scores on extraversion prefer to display positive emotions and to make positive judgments, especially in difficult situations (i.e., cesarean procedure and medical recovery) (Rafienia et al, 2008; Tamir, 2009). These automatic strategies could lead to discrepancies between what people feel and what they display, thus they are maladaptive and may determine psycho-pathological symptoms (i.e., anxiety, depression, psychotic symptoms; Mauss et al, 2007; Marszał-Wiśniewska and Nowicka, 2018). Future research should also assess whether the emotional regulation strategies would explain the relation between extraversion and postnatal psycho-pathological symptoms (i.e., anxiety, depression) on samples of new mothers who experienced the cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that people with high scores on extraversion prefer to display positive emotions and to make positive judgments, especially in difficult situations (i.e., cesarean procedure and medical recovery) (Rafienia et al, 2008; Tamir, 2009). These automatic strategies could lead to discrepancies between what people feel and what they display, thus they are maladaptive and may determine psycho-pathological symptoms (i.e., anxiety, depression, psychotic symptoms; Mauss et al, 2007; Marszał-Wiśniewska and Nowicka, 2018). Future research should also assess whether the emotional regulation strategies would explain the relation between extraversion and postnatal psycho-pathological symptoms (i.e., anxiety, depression) on samples of new mothers who experienced the cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the underlying theory that considers N and E for the regulation of negative and positive mood, respectively, and that mood regulation is the major characteristic of trait EI. Also, N and E are the stronger personality traits than other traits that might be correlated with lower levels of personality hierarchy, trait EI (5,13,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a pre-induction estimate may produce an order effect that requires counterbalancing the presentation of the conditions. However, it cannot be guaranteed that both joyful and sad participants will return to a neutral mood at an equivalent time because of the individual differences in mood regulation capabilities (Marszał-Wiśniewska & Nowicka, 2018). Therefore, the inclusion of a second estimate would require two mood manipulations for each participant (before and after the first estimate).…”
Section: Study Limitationsmentioning
confidence: 99%